Safflor yellow A protects vascular endothelial cells from ox-LDL-mediated damage. (2nd January 2022) - Zhang, Hu; Fan, Li-Juan; Liu, Jun; Zhu, Jia-Qi; Tan, Ting-Ting; Li, Ming; Zhou, You-Li
Abstract: Atherosclerosis is a chronic disease of arteries, which constitutes the pathological basis of a series of cardiovascular diseases. The inflammatory response of vascular endothelial cells mediated by oxidized low density lipoprotein (ox-LDL) is the early behavior and main signal of atherosclerosis. In this study, the damage model of vascular endothelial cells treated with ox-LDL was used to reproduce the damage process of vascular endothelial cells in the process of atherosclerosis. Cell viability was detected by CCK-8. The release levels of reactive oxygen species, nitric oxide, and superoxide dismutase (SOD) were detected by commercial kits. EdU cell proliferation assay was used to detect cell proliferation, real-time fluorescent quantitative PCR and Western blot were used to detect the expression level of related genes. The results showed we successfully constructed a vascular endothelial injury model by incubating vascular endothelial cells with gradient concentrations of ox-LDL. The incubation of safflor yellow A (SYA) partially restored the loss of viability of vascular endothelial cells mediated by ox-LDL, and SYA could promote the proliferation of injured vascular endothelial cells. In addition, SYA may transmit related signals through the AMPK pathway to protect vascular endothelial cells from ox-LDL-mediated damage. All these results provide a further understanding of the occurrence and development of atherosclerosis, provide a theoretical basis for the use of SYA-related drugs in the treatment of cardiovascular diseases, and provide a reference paradigm for studying the pharmacology, toxicology, and mechanism of action of key active substances in TCM.